(untitled) (Sains Humanika, 2019)
Language can emerged within two types; spoken or written language. The ethnic diversity in Sarawak has caused the emergence of various languages or and very significantly to be studied such as the synonym aspect in Iban and Salako languages. Although the languages of the Iban community and Salako communities in Lundu and Sematan area are believed/assumed originated from the same language known as the Austronesian language, but the language spoken daily is different as a result of various factors. The dissimilar elements are in terms of pronunciation, spelling, meaning, context of usage and other elements so on. This study was conducted to, understand and investigate whether the Iban and Salako languages have words that are synonymous. This study was conducted using qualitative method such as literature review, interviews, observations, recording, notes and checks were used to obtain complete and detailed information and linguistic data. The findings show that there are some words in the Iban and the Salako languagese have lexical meaning that are synonymous. The meaning of this synonym is clearly understood even when used in different contexts that are not the same as the two communities. In the context of this study, the synonym aspect in the Iban and Salako languages is seen as a means of unifying, harmonizing and facilitating various affairs in their daily lives, especially as they communicate cross-cultural.